A Study and Comparison of Shipment Policies with Repair Options in a Two-Tier Supply Chain Model. Issue 2 (3rd April 2021) - Öztürk, Harun
Abstract: Vendors often sell their products to buyers far away. Frequently, a few products in the lot are found to be imperfect, but because of the distance to the vendor, it is not cost-effective for the buyer to place another order to replace the imperfect products with good ones. These imperfect products are still valuable and can be repaired, so the buyer has them repaired at a nearby shop and restores them to the inventory. The buyer pays a repair charge plus a markup margin. A two-tier supply chain problem will be studied in this paper under the EOQ (Economic Order Quantity) model, considering the issues of a single buyer and a single vendor and aiming to minimize the total costs for both entities. Based on three supply-chain structures, this paper presents three models, providing engineering managers with guidelines for the selection of a cost-effective supply chain inventory system through analysis of different shipment policies. The shipment policies used for these models were, first, equal-sized, then geometric, and finally, geometric-then-equal-sized. The total expected cost per unit time under each policy is calculated and a proposal is developed for the solution procedure. The paper then proceeds to make a comparative analysis of the three shipment policies in the context of the two-tier supply chain problem. A discussion of the results is illustrated by a numerical example.